The price of federalism - Peterson, Paul E. (Washington, D.C. : Brookings Institution, 1995)
What level of government should be responsible for welfare, education, transportation, and other programs? What are the proper roles of the local, state, and national government? What price do we pay for our federal system? Does federalism perpetuate social inequality? Does it stifle economic growth? More intensely than ever, these questions are at the center of ongoing debate in Congress, statehouses, and town meetings. In this important book, Paul E. Peterson, one of the nation's leading experts on urban problems and American government, addresses them by bringing together two theoretical perspectives on federalism: functional and legislative. He uses these perspectives to explain the changes in federalism that have occurred over the past thirty-five years and to examine the proposals included in the Republican "Contract with America."
After showing how both theories help explain American federalism, Peterson concludes that the federal system has been evolving in a functional direction. As the costs of transportation and communication have declined, labor and capital have become increasingly mobile, placing states and localities in greater competition with one another. State and local governments are responding to these changes by overlooking the needs of the poor and focusing instead on economic development. Meanwhile, the national government has concentrated on social welfare policy. From this perspective, Peterson evaluates the Republican "Contract with America." He applauds its commitment to decentralizing transportation, education, and other basic services to state and local government. But he says that passing the responsibility for welfare to the states would only induce among them a "race to the bottom."
The evolution of modern federalism -- Functional and legislative theories of federalism -- The changing federal system -- Why states choose different policies -- Welfare: a race to the bottom? -- National grants: is equity possible? -- Big cities: is the problem financial? -- Reducing the price of federalism.
"A Twentieth Century Fund book."
Includes bibliographical references (pages 219-231) and index.
Print version record.
English.
JSTOR
Keywords: Federal government -- United States; Federal government; POLITICAL SCIENCE -- General; POLITICAL SCIENCE -- American Government -- General; Federal government; United States; Federalisme; Verenigde Staten; Administracao federal